PENERAPAN KESELAMATAN DAN KESEHATAN KERJA PADA CV. CIPTA MANDIRI DI KABUPATEN KENDAL - Setiawan, Muhammad Nanang; Hariyono, Widodo; Mulasari, Surahma Asti (Jurnal Kesehatan Masyarakat (Journal of Public Health), 2011)
Background: the realization management health and occupational very important to a company. In the CV Cipta Mandiri still occured job accident that can damage employee although facilities that available. As long as CV Cipta Mandiri has perform management system safety and health occupational until necessary does evaluation of realization system. Method: this research constitute of descriptive research with planning cross sectional. The collect of data with does analysis direct on field and interview going deep to researce person. Result : the facilities of work is good, but it need completed wirh maintanance for good function. The company have comitment for does management system safety and job safety program for prevent occupational accident, such as training and counseling. Generally, realization of apply safety and system can run well. Conclusion: the management system of safety and healthy job includes having good facilities. Comitment of the company and the program of preventing accident in a job has been run well, but there must be luck in other aspect that must be improved. Keywords: health, occupational, safety, implementation